The Kalajoki dune field on the west coast of Finland - Olavi Heikkinen; Matti Tikkanen (Fennia: International Journal of Geography, 1987)
The Kalajoki dune field, located on the coast of the Gulf of Bothnia in the area of most rapid land uplift in Finland, is one of the largest active blown sand areas in the country. The morphology of the area and the material composition, internal structure and genetic relations of its deposits are studied here from maps, air photographs, field observations and grain size analyses. Radiocarbon dating and dendrochronology are used to trace the history of' the area and determine the nature of' the aeolian processes.